Improving Educational Experiences for Children in Our Care: An Ethic of Hospitality - Janzen, Melanie; Levine, Kathryn; Sutherland, Dawn (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
The number of children in care in Canada is at epic proportions. Children in care perform at lower rates academically and have far lower graduation rates than children not in care. As children in care enter our schools at increasing rates and experience poor school success, it is of dire importance to understand how to better support these children. Drawn from a larger study seeking to improve systems change for children in care, this aspect of the study focused on school leaders’ strategies for improving the experiences of children in care in their schools. Using Derrida’s and Ruitenberg’s articulations of an ethic of hospitality, we will illustrate participants’ experiences and argue for the need for the education system to more justly engage in ethical relations with children, particularly those who are most vulnerable. Keywords: children in care, foster care, ethical engagements, hospitality